Expressions of Transforming Growth Factor β1 Signaling Cytokines in Aortic Dissection - Yuan,Shi-Min (2018)
Abstract Objective: To demonstrate the underlying mechanisms of aortic dissection compared to those of coronary artery disease in terms of the transforming growth factor-beta (TGF-β) signaling pathway. Methods: Twenty consecutive aortic dissection patients and 20 consecutive coronary artery disease patients undergoing a surgical treatment in this hospital were enrolled into this study. The aortic tissues were sampled and the TGF-β1 and its receptor TGF-β receptor I (TβRI) were detected by Western blotting assay. Results: TGF-β1 and TβRI were positively expressed in the aortic tissues in both groups by Western blotting assay. The expressions of the two proteins were significantly higher in the aortic tissue of patients with aortic dissection than in those with coronary artery disease. The quantitative analyses of the relative gray scales of the proteins disclosed close correlations between the expressions of TGF-β1 and TβRI in both the study and control group patients. Conclusions: The aortic remodeling of aortic dissection might differ from that of coronary artery atherosclerosis concerning the nature, mechanism, mode, and activities of TGF-β signaling pathway. The development of aortic dissection could be associated with a significantly enhanced function of TGF-β1/Smad signaling transduction as a result of aortic remodeling incorporating both vascular injury and repair.